Gene target selection for loop-mediated isothermal amplification for rapid discrimination of Treponema pallidum subspecies. - Sascha Knauf; Simone Lüert; David Šmajs; Michal Strouhal; Idrissa S Chuma; Sieghard Frischmann; Mohammed Bakheit (Public Library of Science (PLoS), 2018)
We show proof of concept for gene targets (polA, tprL, and TP_0619) that can be used in loop-mediated isothermal amplification (LAMP) assays to rapidly differentiate infection with any of the three Treponema pallidum subspecies (pallidum (TPA), pertenue (TPE), and endemicum (TEN)) and which are known to infect humans and nonhuman primates (NHPs). Four TPA, six human, and two NHP TPE strains, as well as two human TEN strains were used to establish and validate the LAMP assays. All three LAMP assays were highly specific for the target DNA. Amplification was rapid (5-15 min) and within a range of 10E+6 to 10E+2 of target DNA molecules. Performance in NHP clinical samples was similar to the one seen in human TPE strains. The newly designed LAMP assays provide proof of concept for a diagnostic tool that enhances yaws clinical diagnosis. It is highly specific for the target DNA and does not require expensive laboratory equipment. Test results can potentially be interpreted with the naked eye, which makes it suitable for the use in remote clinical settings.